2021
DOI: 10.15416/ijcp.2021.10.3.172
|View full text |Cite
|
Sign up to set email alerts
|

The Beyond-Use Date Perception of Drugs in North Jakarta, Indonesia

Abstract: Beyond-Use Date (BUD) refers to the unsafe period of drug consumption and is calculated from the moment of opening the primary package. Meanwhile, Indonesia has no current related data, in terms of public awareness. Therefore, this research aims to assess the BUD perception of North Jakarta communities and pharmacists’ roles in providing the relevant information. The data collection process employed a semi-structural interview across 6 districts in the research location between September-November 2019, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(16 reference statements)
1
4
0
1
Order By: Relevance
“…Kusuma et al (2020) reported that the level of public knowledge related to the Beyond Use Date in Indonesia is still relatively low. This was also confirmed by Cokro et al (2021), who reported that the majority of the respondents examined (97%), did not know about BUD, and all respondents (100%) never received information on BUD from pharmacists. Some of the respondents have the perception that BUD is the same as the expiration date which is usually printed on the factory packaging.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Kusuma et al (2020) reported that the level of public knowledge related to the Beyond Use Date in Indonesia is still relatively low. This was also confirmed by Cokro et al (2021), who reported that the majority of the respondents examined (97%), did not know about BUD, and all respondents (100%) never received information on BUD from pharmacists. Some of the respondents have the perception that BUD is the same as the expiration date which is usually printed on the factory packaging.…”
Section: Introductionsupporting
confidence: 53%
“…Some of the respondents have the perception that BUD is the same as the expiration date which is usually printed on the factory packaging. Cokro et al (2021) concluded that the perception of the people of North Jakarta regarding BUD could be caused by the low knowledge of BUD, and thus, the role of pharmacists in informing and educating patients and the public about BUD is very necessary.…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study on BUD knowledge of the North Jakarta community found that approximately 50% of the informants consider BUD and the expiration date similar. 6 This result shows that there is a need to promote Indonesian pharmacists on having sufficient BUD knowledge and delivering the information to patients. This study emphasizes the importance of repeating and updating BUD information through various education development programs regulated by The Indonesia Pharmacist Association.…”
Section: Discussionmentioning
confidence: 94%
“…According to the recent study by Cokro et al (2021), the comprehension of BUD among the North Jakarta community in Indonesia is extremely low, as only 3% have sufficient knowledge, and none of the respondent mentioned pharmacists as a source of BUD information. 6 This study aims to examine the prevalence of Indonesian pharmacists’ knowledge of BUD of various non-sterile compounding drugs since this problem has not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study conducted in Yogyakarta found that 75% of prescriptions intended for children can only be carried out through extemporaneous compounding due to the non-availability of readily made dosage forms, 8 hence, this re-emphasize that the knowledge of BUD is very important for patients. 9 According to Cokro et al 9 from a total of 60 informants, 97% know nothing about BUD, while 100% denied pharmacists’ role in providing related information. Therefore, there is a need to study BUD interventions from the pharmacist angle, that is, providing BUD information on drug labels and verbally.…”
Section: Introductionmentioning
confidence: 99%